Laparoscopic Treatment of 1522 Adnexal Masses: An 8-Year Experience. (11th February 2015) - Grammatikakis, I.; Trompoukis, P.; Zervoudis, S.; Mavrelos, C.; Economides, P.; Tziortzioti, V.; Evangelinakis, N.; Kassanos, D.
Abstract : Objective . To reevaluate the long-term effectiveness and safety of laparoscopy in benign ovarian pathology. Materials and Methods . 1522 women with benign adnexal cysts, laparoscopically treated in the 3rd Department of Ob/Gyn, General University hospital "Attikon" and "Lito" Maternity Hospital between July 1998 and December 2006, were included. Results . The diagnosis in 1222 (80, 6%) cases was endometriosis of the ovary, 60 (4%) hydrosalpinx, 51 (3, 3%) serous cystadenomas, 44 (2, 9%) dermoid ovarian cyst, 38 (2, 5%) borderline tumors, 35 (2, 3%) unruptured follicles, and 33 (2, 2%) paraovarian cysts. In 174 cases (11, 5%) laparoscopy was converted to laparotomy due to technical difficulties or suspicion of cancer. In particular, laparotomy was performed in 119 (8%) women due to severe adhesions and 18 (1, 2%) women due to bleeding that could not be controlled safely by laparoscopy. In 36 (2, 4%) women frozen section during operation revealed malignancy and laparoscopy was converted to laparotomy. A few operative complications were recorded like post-op fever, small hematomas at the trocar entries. Conclusions . Laparoscopic surgery seems to offer significant advantages such as reduced hospital stay, less adverse effects, better quality of life, and superior vision especially on surgical treatment of cases like endometriosis.